UPAYA MENINGKATKAN KEAKTIFAN BELAJAR MELALUI PERMAINAN SEDERHANA BERBASIS GAME-BASED LEARNING PADA MURID KELAS 1 SDN 2 LOKTABAT SELATAN - Talitha Hidayanti; Rahmadi; Fakhruddin; Sujarwoko; Fani Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Student engagement in Physical Education, Sport, and Health (PJOK) learning among first-grade students at SDN 2 Loktabat Selatan was found to be relatively low. This condition was reflected in the limited participation of studentss during lessons, their lack of confidence in performing movement activities, and their minimal involvement throughout the learning process. Therefore, this study was conducted to improve students’ learning engagement through the implementation of through the implementation of simple Game-Based Learning activities in PJOK lessons. This research employed the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which includes four stages: planning, action, observation, and reflection. The participants were 28 first-grade students in the second semester of the 2025/2026 academic year. Data were collected through observation using a learning engagement observation sheet covering physical, verbal, mental, emotional, and social aspects. The collected data were analyzed descriptively using percentage calculations to determine the level of student engagement in each research cycle. The findings revealed that the use of simple Game-Based Learning activities successfully improved student engagement in learning. In the pre-cycle stage, the level of learning engagement was categorized as moderately active. After the implementation of the intervention in Cycle I, student engagement increased to the active category. These findings indicate that simple Game-Based Learning activities can serve as an effective instructional strategy for enhancing student engagement in PJOK learning at the elementary school level.